Controllable hydrophilicity-hydrophobicity and related properties of konjac glucomannan and ethyl cellulose composite films. (June 2018) - Wu, Kao; Zhu, Qian; Qian, Hong; Xiao, Man; Corke, Harold; Nishinari, Katsuyoshi; Jiang, Fatang
Abstract: An improved preparation method of konjac glucomannan-ethyl cellulose (KGM-EC) composite film was adopted to allow hydrophobic contents (EC) varying from 0% to 85.7% in the films, and may be explained by emulsification effect of both KGM and EC. Scanning electron microscopy images supported that all blend films had homogenous microstructures without phase separation. Moisture adsorption, water contact angle, swelling test, water vapor transmission, and mechanical tests were performed to evaluate the hydrophilicity-hydrophobicity and related properties of the films. Results indicated that EC addition significantly decreased the values of moisture adsorption, swelling, water vapor transmission, and mechanical strength of the films, and increased the contact angle. For composite films, linear relationships (most R 2  > 0.9) were found between ingredient proportion and results of moisture isotherms, and water contact angle, indicating controllable hydrophilicity-hydrophobicity. Ingredient proportion was also found to correlate linearly with film tensile strength (TS) and elongation ratio (R 2  = 0.7502 and 0.8974, respectively), and after immersion in water, TS still correlated linearly with ingredient ratio (R 2  = 0.9767). These results support the hydrophilicity-hydrophobicity and related properties of KGM-EC film could be controllable through ingredient proportion, and this also offers the potential of the film to have unique property changes (e.g. linear) in response to different relative humidity or a w equilibrium condition under certain ingredient proportion. Graphical abstract: Image Highlights: Novel films with varying hydrophobic characters were prepared based on KGM and EC. Film mechanical properties were linearly related to ingredient proportions. The controllable film properties provide promising application prospects.